2008
DOI: 10.1097/paf.0b013e31815b4d37
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Findings in Cases of Sudden Death Due to Blunt Cardiac Trauma—‘Commotio Cordis’

Abstract: Commotio cordis is a term used for cases of sudden cardiac death due to nonpenetrating chest trauma without evidence of underlying myocardial disease or injury. Contusio cordis has been reserved for cases of chest trauma where there is cardiac bruising. Three deaths due to blunt cardiac and chest trauma after vehicle accidents are presented where the only significant injuries were contusions of the heart and fractures of the sternum and ribs. One case had moderate coronary artery atherosclerosis and another ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Although the intention is not to include traumatic causes of sudden death, commotio cordis (sudden death following blunt trauma to the chest) is worthy of mention as the history may not be forthcoming without consideration and direct questioning [240][241][242][243][244].…”
Section: Sudden Cardiac Death: Other Aetiologiesmentioning
confidence: 99%
“…Although the intention is not to include traumatic causes of sudden death, commotio cordis (sudden death following blunt trauma to the chest) is worthy of mention as the history may not be forthcoming without consideration and direct questioning [240][241][242][243][244].…”
Section: Sudden Cardiac Death: Other Aetiologiesmentioning
confidence: 99%
“…A focal area of atherosclerosis was found in the left anterior descending coronary artery causing 50% stenosis. In author's view, underlying cardiac disease in that case was not sufficient to cause death alone and might therefore would have predisposed to death from commotio/contusio cordis (20).…”
Section: Resultsmentioning
confidence: 91%
“…27 It has been recently suggested that the separation of blunt impact without demonstrable injury to the heart, so-called "commotio cordis", from those cases where there is bruising or associated injury is a somewhat artificial classification, as cases are in practice all part of an overlapping spectrum of merging injuries. 17 The diagnosis of coronary artery rupture can be made by Doppler echocardiography, 21 and pericardial tamponade and cardiac lacerations can be diagnosed by transthoracic or transoesophageal echocardiography. In severe blunt chest trauma, emergency thoracotomy permits rapid diagnosis and immediate surgical repair of cardiac injuries and has been shown to improve the prognosis even in patients with massive cardiac injuries.…”
Section: Discussionmentioning
confidence: 99%